On fossil plants collected by Mr. R.A. [i.e. R.G.] McConnell, on Mackenzie River, and by Mr. T.C. Weston, on Bow River [electronic resource] - Dawson, J. W. (John William), Sir, 1820-1899.; Royal Society of Canada. ([S.l. : s.n., 1889)
Caption title. At head of title: Section IV, 1889. Trans. Roy. Soc. Canada. "(Read May 7, 1889.)" Electronic reproduction. Mode of access: Internet. 44